Liver and Splenic Volumes in the Indian Population: Is There a Single CT Measurement Correlate? - Anitha Jasper (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Several techniques using Computed Tomography (CT) have been used to determine liver and splenic volumes/ sizes. Aim: To calculate liver and splenic volumes in patients with normal livers and spleens on cross-sectional imaging and determine if there is a single CT measurement index that can correlate with liver or splenic volume. Materials and Methods: This was a retrospective study in which liver and splenic volumes were measured using CT in 100 patients. Volumes were obtained by summing the area of the liver or spleen on each section and multiplying it by the image reconstruction interval using available software. The relationship between liver and splenic volumes with various unidimensional indexes and other variables were assessed using Pearson’s correlation coefficient. Linear regression equations were obtained to correlate these indices with liver and splenic volumes. Results: Mean liver and splenic volumes were 1281±219 cm3 and 194.6±78 cm3 respectively. The upper limit of normal for the anteroposterior diameter of the liver was 16.15 cm (r=0.56, p-value <0.001) and the upper limit of normal for splenic length was 10.81 cm (r=0.74, p-value <0.05). Multi-dimensional indices correlated better with liver and splenic volume than the unidimensional indices. A significant positive correlation was seen between the height, weight, Body mass index (BMI) and Body Surface Area (BSA) of the patient with liver volume; however, no significant correlation was seen between height, weight, BMI and BSA with splenic volume. Conclusion: In this study, authors have determined that the antero-posterior diameter of the liver of 16.15 cm and splenic length of 10.81 cm are simple measurements which can be used as reliable indicators of hepatosplenomegaly during routine practice.